UTILIZATION TOGAF ADM FOR ENTERPRISE ARCHITECTURE MODEL DESIGN - Yunis, Roni; Surendro, Kridanto; S. Panjaitan, Erwin (Jurnal Ilmiah Informatika Komputer, 2009)
The purpose of enterprise achitecture is to develop harmony between business and information technology fororganization, enterprise architecture implementation can not avoid mehtod of organization planning and howto design the enterprise architecture. Design of enterprise architecture need a methodology, many organizationshave limited understaning of methodology steps for enterprise architecture design. The step in enterprisearchitecture is very important and continue to implementation. The output is to develop an enterprisearchitecture which used by an organization to achieve the strategy target.Keyword(s): business architecture, data architecture, enterprise architecture, technology architecture,implementation architecture, TOGAF ADMSubject Description : K.6.Management of Computing and Information Systems | K.6.1.Project and PeopleManagement | Systems Development